Ground improvement for ring beam tank foundation compared between vibro replacement against combination of dynamic techniques with numerical models - Khan, Adil (2019)
Construction of large tanks are often carried out implementing a ring beam foundation. Majority of the load is transferred the ground, therefore, in areas of poor ground conditions, additional measures are taken to avoid geotechnical failure. Various methods exist for ground improvement, however, techniques such as piling and Vibro-Replacement are commonly implemented, due to their deep depth of improvement and flexibility of applicability for a wide range of soil profiles. However, alternative techniques may be implemented which could prove more efficient and even cost effective. Dynamic techniques, due to their fast rate of production, reduced operation costs and impressive efficiency prove as viable options. But since dynamic techniques have limitations with soil type and depth of improvement, for stratified geotechnical profiles, they may only be carried out in a combination with one another, which may deter engineers for opting to implement them. In the current study, the efficiency of ground improvement for a ring beam tank foundation shall be compared between Vibro-Replacement against combination of dynamic techniques with numerical models, to provide an insight between their capabilities and preliminary cost estimations shall also be carried out to a lesser extent to get an idea of the economic factors that affect decision making for ground improvement operations.